2022
DOI: 10.5038/2771-5957.1.1.1001
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of implementing green HRM practices on environmental performance: The moderating role of green process innovation

Abstract: As the world is trying to curb CO2 emission, mainly from the industries, various organizations' employees are crucial in mitigating carbon monoxide emissions. The employee reaction based on their perception of human resources management practices shapes their commitment to the workplace environment. According to relevant environment literature, emphasizing effective environmental management improves employees' green attitudes dedicated to natural purposes. This study explores how to enhance hotels' environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…We expected to observe a meaningful influence relationship between variables and green performance. To sum up, based on existing studies [ 15 , 28 , 29 , 30 ] that have attempted to predict employees’ behavior based on green human resource management applied with the AMO model in the hotel industry, the mediating function of green psychological climate was additionally confirmed. In addition, the importance of CSR, mentioned above, is differentiated from existing studies by confirming the mediating function of CSR perceived by employees, not at the customer level, by verifying the influence relationship between variables from two dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…We expected to observe a meaningful influence relationship between variables and green performance. To sum up, based on existing studies [ 15 , 28 , 29 , 30 ] that have attempted to predict employees’ behavior based on green human resource management applied with the AMO model in the hotel industry, the mediating function of green psychological climate was additionally confirmed. In addition, the importance of CSR, mentioned above, is differentiated from existing studies by confirming the mediating function of CSR perceived by employees, not at the customer level, by verifying the influence relationship between variables from two dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…This method is appropriate for use when there is a concern about heterogeneity, as it is robust to omitted variables, endogeneity, non-stationarity, and cross-sectional dependence, among other characteristics ( 80 , 81 ). This approach proposes that the conventional ARDL approach be supplemented by including their lags, dependent variable, and cross-section averages of covariates in addition to the traditional ARDL approach.…”
Section: Methodology and Datamentioning
confidence: 99%
“…The majority of the currently available studies focus on the influence that environmental governance has on its interaction with environmental regulation. Those cities that prioritize protection of the environment are more vulnerable to the effects of less stringent environmental regulations in their neighboring cities, according to the research results of ( 54 ). It has been suggested that regional competition could significantly decrease haze control's effectiveness Irani and Kilic ( 55 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This paper and Dudek and Spiewak ( 65 ) both analyze the impact on regional environmental quality from government governance and public participation. However, Irani and Kilic ( 54 ) only focused on characterizing government environmental governance from the implementation of local government environmental responsibility goals, and they neglected the combined effect that public participation has on government governance. This paper analyses the impact on regional environmental quality from the perspectives of public participation and government governance.…”
Section: Literature Reviewmentioning
confidence: 99%